Facilitating Healing in Diabetic Foot Ulcers Using Homeopathy in a Multi-Disciplinary Integrative Approach: Two Evidence-Based Case Reports - Ponnam, Hima Bindu (Homeopathy, 2024)
Background A rising incidence of diabetic foot ulcers (DFUs) in India has escalated the rate of lower limb amputations in the country. The present study aims to evaluate the potential healing properties of homeopathic medicines as a part of the integrative management of DFUs through two evidence-based case reports.Methods Two patients with DFUs, identified as Wagner grade 2, having had diabetes for 12 years, were treated with individualized homeopathic medicine within a multi-disciplinary approach. Both cases were on oral hypoglycemic agents for managing blood sugar, continued their diabetic medication, and were advised to use regular wound dressings. The DFUs were assessed using the Pressure Ulcer Scale for Healing (PUSH) score at baseline and every 4 weeks until complete wound healing. Neuropathic changes were evaluated by the 10g monofilament tactile test, and the Modified Naranjo Criteria for Homeopathy—Causal Attribution Inventory (MONARCH) tool was used to assess the likelihood of there being a causal relationship between clinical improvement and the homeopathic intervention.Results The DFUs showed healing within 12 weeks, with a significant improvement in the PUSH score, though there was no change in tactile sensation as assessed by the monofilament test. The MONARCH tool yielded +9 in both cases, indicating the likelihood of a causal relationship between the clinical outcome and homeopathic intervention. The homeopathic medicines Arsenicum album and Lachesis respectively were found useful by each patient.Conclusion Homeopathy appeared beneficial in facilitating the early healing of DFUs within a multi-disciplinary integrative approach.
Keywords: Arsenicum album; Lachesis; Homeopathy; Diabetic foot ulcer; Pressure Ulcer Scale for Healing